On-The-Flight trapping, LIBS analysis and discrimination of single meteorite particles generated by laser ablation - Burgos-Palop, Clara; Fortes-Román, Francisco Javier; Purohit Pacheco, Pablo; Delgado-Pérez, Tomás; Laserna-Vázquez, José Javier (Elsevier, 2024)
Results: Bulk meteorite samples were directly ablated within an ablation cell. From few micrograms of ablated matrix, we originated dry aerosols consisting of multielemental particles which were representative of the sample chemistry. SEM images confirmed that the generated particles exhibited spherical geometry. Particles were first optically trapped in air and, then, analyzed by laser-induced breakdown spectroscopy (LIBS). LIBS spectra evidenced compositional differences among samples. For example, Campo de Cielo meteorite featured a high iron content due to its metallic nature whereas LIBS results for Jbilet Winselwan and NWA 869 suggested that pyroxene components dominated the composition of the samples. In contrast, NWA 13739 and Vaca Muerta contained high aluminum intensity, thus indicating that the feldspathic component was dominant, as then verified by XRD. The intra-sample compositional variability were quite satisfactory, as revealed by the RSD data, below 45 %. For quantitative analysis, the percentages of FeO, SiO2, Al2O3, Na2O, MgO, TiO2, CaO, K2O, MnO, SrO, Cr2O3, and Li2O were calculated using CF-LIBS. Significance: This work demonstrates the applicability of laser excitation of individual particles in an optical trap for the multielemental analysis of meteorites. The methodology provides a complete overview of the samples, is capable of classificating them according to their main phases and yield preliminary quantitative information about those phases. Therefore, we present a minimally destructive pathway to be used as the first step in the inspection of these delicate samples. If the particles represent nanostructures inherent to the meteorites, it would constitute a major step in the analysis of extraterrestrial material that may provide fundamental insights into the structure and composition of the original materials at the microscale, a topic that remains an active area of research worldwide.
Keywords: Espectroscopía de plasma inducido por láser; Laser ablation; Optical trapping; LIBS; Meteorite; Single-particle analysis